Growth variability in seedlings of eight provenances of Abies religiosa (H.B.K.) Schlecht. et Cham., in nursery conditions - Benavides-Meza, Héctor Mario; Gazca Guzmán, Maira Oriana; López López, Stephanie Fabiola; Camacho Morfín, Francisco; Fernández Grandizo, Diana young; de la Garza López de Lara, María del Pilar; Nepamuceno Martínez, Felipe (Instituto de Ecología, A.C., 2016)
Abies religiosa shows a wide distribution in Mexico and extends from the States of Sinaloa and San Luis Potosí in the north part of Mexico up to Puebla and Tlaxcala in the south, but there are also populations of this species in Guatemala. The forests in the Valle de México region are located in the mountainous areas around Mexico City and socially and ecologically are very important because they are a significant component of the periurban forest of this Metropolitan Area. Unfortunately these stands have been declining for the last 30 or more years and it is imperative to look for solutions to restore these areas. The objective for this project was to determine the variation in growth (height and basal diameter) among eight provenances of this species and was used a random block design with 64 replicates. Measurements were done every three months through a period of a year. Seedlings from San Nicolás Coatepec provenance showed the top values in height (37,2 cm), however the growth rate was only significantly different with Cofre de Perote. The biggest basal diameter growth was recorded in seedlings from Coatepec (DISEFO) provenance, and it was significantly different from the rest of provenances, but no pattern of geographicallydetermined variation was observed among the growth response from the different  provenances.